Examining if the relationship between BMI and incident type 2 diabetes among middle–older aged adults varies by race/ethnicity: evidence from the Multi‐Ethnic Study of Atherosclerosis (MESA). Issue 5 (22nd September 2020) - Rodriguez, L. A.; Bradshaw, P. T.; Shiboski, S. C.; Fernandez, A.; Vittinghoff, E.; Herrington, D.; Ding, J.; Kanaya, A. M.
Abstract: Aims: Disparities persist on the prevalence of undiagnosed type 2 diabetes in racial/ethnic minorities in the USA. This study evaluated the association between BMI and incident type 2 diabetes risk by racial/ethnic group, to determine whether BMI and presence of type 2 diabetes risk factors may help clinicians better target type 2 diabetes screening. Methods: This prospective cohort analysis included 5659 adults free of type 2 diabetes at baseline from the Multi‐Ethnic Study of Atherosclerosis (MESA), a population‐based cohort (2000–2011). BMI was measured at baseline and time‐updated at subsequent visits. Incident type 2 diabetes was defined as fasting glucose ≥ 7.0 mmol/l, or use of any diabetes medications. Results: The mean (sd ) age was 62 (10) years and 42% of participants were white, 26% African American, 20% Hispanic and 12% Chinese American. During follow‐up, 696 (12%) new type 2 diabetes cases were observed. In age‐ and sex‐adjusted models, in the presence of one or more type 2 diabetes risk factors (the most common scenario), a 10% risk of incident type 2 diabetes was observed at a BMI of 21.7 kg/m 2 [95% confidence interval (CI) 20.1 to 22.8] in Chinese Americans, 23.8 kg/m 2 (22.7 to 24.9) in Hispanics, 24.7 kg/m 2 (23.7 to 25.6) in African Americans and 26.2 kg/m 2 (25.1 to 26.9) in white participants. Conclusions: This study supports including BMI and presence of type 2 diabetes risk factors as action points for clinicians to prioritize which adults aged ≥ 45 years should be screened. The application of race/ethnicity‐specific BMI thresholds may reduce the disparity of undiagnosed type 2 diabetes observed in minority groups.